Urban ecology - Gaston, Kevin J.; Barton, Jo; Bates, Adam; Boone, Christopher; Davies, Zoe G.; Edmondson, Jill L.; Evans, Karl L.; Fuller, Richard A.; Hale, James; Harlan, Sharon L.; Irvine, Katherine N.; James, Philip; et al. (Ecological reviews, 2010)
"This is the urban century in which, for the first time, the majority of people live in towns and cities. Understanding how people influence, and are influenced by, the 'green' component of these environments is therefore of enormous significance. Providing an overview of the essentials of urban ecology, the book begins by covering the vital background concepts of the urbanisation process and the effect that it can have on ecosystem functions and services. Later sections are devoted to examining how species respond to urbanisation, the many facets of human-ecology interactions, and the issues surrounding urban planning and the provision of urban green spaces. Drawing on examples from urban settlements around the world, it highlights the progress to date in this burgeoning field, as well as the challenges that lie ahead"--